A Corpus-Based Evaluation Approach to Translation Improvement - Hassani, Ghodrat (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
In professional settings translation evaluation has always been weighed down by the albatross of subjectivity to the detriment of both evaluators as clients and translators as service providers. But perhaps this burden can be lightened, through ongoing evaluator feedback and exchange that foster objectivity among the evaluators while sharpening the professional skills and recognition of the translators. The purpose of this paper is to explore the promising avenues that a corpus-based evaluation approach can possibly offer them. Using the Corpus of Contemporary American English (COCA) for evaluation purposes in a professional setting, the approach adopted for this study regards translation evaluation as a means to a worthwhile end, in a nutshell, better translations. This approach also illustrates how the unique features of the corpus can minimize subjectivity in translation evaluation; this in turn leads to translations of superior quality.